UJI RESISTENSI BAKTERI PSEUDOMONAS SP YANG DI ISOLASI DARI PLAK GIGI TERHADAP MERKURI DAN TETRASIKLIN - Simangunsong, Yoas P.; Bodhi, Widdhi; Kepel, Billy J. (eBiomedik, 2015)
Abstract: Food and even water are commonly exposed to mercury in the environment. Mercury is a highly toxic element either in the element or compound forms. One of the methods used to detoxify mercury is by using mercury-resistant microorganisms, such as mercury-resistant bacteria. This can occur when mercury is exposed to the human body in a low level for a long time. This condition enables the bacteria inside the human body to adapt and even reduce the mercury level, therefore, lowering its risk consequently. This study aimed to find out whether Pseudomonas sp. was resistant to mercury and tetracycline. Mercury-resistance test of Pseudomonas sp. was conducted by using liquid Luria-Bertani (LB) media which had been incubated for 24 hours. The results showed that bacterial colonies were found in 10 ppm, 20 ppm, and 40 ppm of diluted HgCl2 which indicated its resistance. However, in 80 ppm of dilution there was no growth of bacterial colony. Tetracycline-resistance test used solid LB media that had also been incubated for 24 hours. The results showed the antibiotic inhibition zone of tetracycline was 27 mm. Conclusion: Pseudomonas sp. was resistant to diluted HgCl2 until 40 ppm, but was not resistant to diluted HgCl2 80 ppm and tetracycline.Keywords: Pseudomonas sp., mercury, tetracycline, bacteria resistanceAbstrak: Baik makanan maupun sumber air sering telah terpapar dengan merkuri yang sangat bersifat toksik baik dalam unsur tunggal maupun senyawa. Salah satu usaha untuk detoksifikasi merkuri ialah dengan menggunakan mikroorganisme resisten merkuri. Hal ini dapat terjadi jika tubuh manusia terpapar merkuri dalam kadar yang kecil untuk waktu yang sangat panjang sehingga bakteri dalam tubuh manusia dapat beradaptasi bahkan mampu mereduksi merkuri tersebut sehingga menjadi tidak toksik. Penelitian ini bertujuan untuk mengetahui apakah bakteri Pseudomonas sp. resisten terhadap merkuri dan tetrasiklin. Untuk uji resistensi merkuri pada Pseudomonas sp. digunakan media Luria-Bertani (LB) cair yang telah diinkubasi selama 24 jam. Pada pengenceran HgCl2 10 ppm, 20 ppm, dan 40 ppm masih ditemukan koloni bakteri (resisten) tetapi pada pengenceran 80 ppm tidak terdapat pertumbuhan koloni bakteri. Uji resisten terhadap tetrasiklin menggunakan media LB padat yang telah diinkubasi selama 24 jam dan didapatkan zona hambat antibiotik tetrasiklin 27 mm (tidak resisten). Simpulan: Pseudomonas sp. resisten terhadap HgCl2 sampai dengan pengeceran 40 ppm, tetapi tidak resisten pada pengenceran 80 ppm dan terhadap antibiotik tetrasiklin.Kata kunci: Pseudomonas sp. , merkuri , tetrasiklin, resistensi bakteri